The riffle beetles (Coleoptera: Elmidae) of the Eocene Baltic amber: Heterelmis groehni sp. nov. and Heterlimnius samlandicus (Bollow, 1940) comb. nov. - Bukejs, Andris; Alekseev, Vitalii I.; Jäch, Manfred A. (Zootaxa, 2015)
The Eocene elmid beetles known from Baltic amber so far are reviewed, and their natural environment is discussed. Palaeoriohelmis samlandica Bollow, 1940 is re-described based on examination of the holotype. The genus Palaeoriohelmis Bollow, 1940 is synonymized with Heterlimnius Hinton, 1935, and Palaeoriohelmis samlandica is transferred to Heterlimnius (H. samlandicus comb. nov.). Heterelmis groehni sp. nov. is described and illustrated. Elmadulescens rugosus Peris, Maier & Sánchez-García, 2015 from Cretaceous Spanish amber is removed from Elmidae.